Copper ion-chelated zwitterionic polymer nanogel and applications thereof
Patent Information
- Application Number
- CN202611307389.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-23
AI Technical Summary
[0008]针对现有铁基纳米酶在肿瘤微环境中催化活性不足、GSH消耗能力有限,以及现有铜基纳米制剂缺乏高效递送载体、难以实现CDT/化疗协同治疗的问题,本发明提供一种铜离子螯合的两性离子聚合物纳米凝胶及其应用
1. 创新的材料设计与配位机制:本发明首次将含邻苯二酚基团的多巴胺单体引入P(MPC-ss-DMA)两性离子纳米凝胶骨架,通过酚羟基与Cu2+的动态配位作用实现铜离子的高效螯合。该配位方式条件温和、动态可逆,避免了共价修饰对纳米凝胶结构的破坏,且具有pH依赖性(生理中性pH条件稳定螯合,弱酸性肿瘤微环境响应性解离),为铜基CDT纳米制剂的构建提供了新策略。
Smart Images

Figure CN122954722A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer biomedical nanomaterials technology, specifically relating to a copper ion-chelated zwitterionic polymer nanogel, its preparation method and application, and particularly to a nanogel system based on the copolymerization of phosphorylcholine zwitterionic monomer and dopamine monomer, which chelates copper ions through phenolic hydroxyl groups and loads antitumor drugs, and its application in tumor treatment. Background Technology
[0002] Cancer remains a major global health threat, and its treatment continues to face significant challenges. Chemodynamic therapy (CDT), through the Fenton reaction, converts hydrogen peroxide (H₂O₂) in the tumor microenvironment (TME) into highly toxic hydroxyl radicals (·OH), offering a novel strategy with fewer side effects for cancer treatment. However, the most widely studied iron-based Fenton reagents have certain limitations: their catalytic efficiency is highly dependent on a strongly acidic environment, and their reactivity is significantly reduced in a weakly acidic TME; simultaneously, the high concentration of glutathione (GSH) within tumor cells rapidly scavenges the generated ·OH, severely weakening the therapeutic effect.
[0003] To address these issues, researchers have turned their attention to copper ions, which exhibit superior catalytic performance. Compared to iron ions, copper ions (especially Cu) offer superior catalytic properties. + The rate constant of the Fenton-like reaction mediated by Cu is higher, and it exhibits better catalytic activity in physiological environments. More importantly, Cu... 2+ Reduced to Cu + During this process, GSH can be effectively consumed, thereby weakening the antioxidant defense capacity of tumor cells and enhancing oxidative stress. Therefore, the development of copper-based nanoparticles is considered an important direction for improving the efficacy of CDT.
[0004] Polymer nanogels are nanoscale dispersed particles formed by physical or chemical crosslinking of hydrophilic polymers, exhibiting extremely high colloidal stability and drug loading capacity. Zwitterionic polymers are a class of polymers containing both anionic and cationic groups on the side chains of the same monomer, resulting in overall electrical neutrality. Nanogels constructed using zwitterionic polymers exhibit superior long-circulation properties in blood compared to polyethylene glycol (PEG) due to their strong hydration ability and resistance to non-specific protein adsorption. Several existing studies have reported on the preparation and application of zwitterionic nanogels. For example, Chinese patent CN108379219A (Fudan University) discloses a biodegradable zwitterionic polymer nanogel prepared by precipitation polymerization of zwitterionic monomers of the sulfobetaine, carboxybetaine, or phosphorylcholine type with a disulfide-containing crosslinking agent, which can be used to load antitumor drugs. Chinese patent CN106810636A (Huazhong University of Science and Technology) discloses a pH-regulated, hydrophobicity-reversal, charge-reversal, and redox-responsive nanogel, which comprises a thermosensitive monomer, a zwitterionic monomer, and an amine-containing pH-sensitive monomer. Chinese patent CN119930924A (Suzhou Jianxiong Vocational and Technical College) discloses a zwitterionic nanogel copolymerized with N-vinylcaprolactam and methacryloylornithine, exhibiting reductive degradation resistance and good anti-protein adsorption ability. None of the above-mentioned prior art involves metal ion chelation for chemokinetic therapy.
[0005] Furthermore, researchers have attempted to combine zwitterionic nanogels with metal ions to construct nanozymes with enzyme-like catalytic activity. For example, Chinese patent CN117467074A (Suzhou Jianxiong Vocational and Technical College) discloses a biodegradable nanozyme based on a zwitterionic polymer gel. It uses 2-methacryloyloxyethylphosphorylcholine (MPC) and methacrylic acid (MAA) as comonomers, prepares a nanogel with a disulfide-containing crosslinking agent, and then uses FeCl2 to chelate the phosphate groups in the nanogel to obtain an iron-based nanozyme, which is used for CDT / chemotherapy synergistic antitumor therapy. However, this iron-based nanozyme still suffers from the inherent defects of iron-based Fenton reagents: its catalytic activity is not ideal in the weakly acidic tumor microenvironment, and its ability to consume GSH is limited, making it difficult to maximize the oxidative stress effect.
[0006] To address the aforementioned shortcomings, the inventors discovered that combining copper ions with zwitterionic nanogels, particularly by introducing monomers containing catechol structures (such as dopamine) into the nanogel framework, allows for the interaction of phenolic hydroxyl groups with Cu. 2+ By forming coordination bonds, copper-based nanoparticles with high catalytic activity, strong GSH consumption capacity, and excellent biocompatibility can be obtained. Compared with iron-based systems, copper ion-mediated Fenton-like reactions remain highly efficient under weakly acidic conditions, and Cu... 2+ Reduced to Cu +The process can synergistically consume GSH, thereby significantly enhancing the efficacy of CDT. Simultaneously, the introduction of zwitterionic nanogels endows the system with good anti-protein adsorption properties and a longer blood circulation time, and can achieve tumor-reducing environment-responsive degradation through disulfide bond cross-linking. Further loading with chemotherapeutic drugs (such as doxorubicin) can achieve synergistic CDT / chemotherapy. Currently, there are no reports on the use of dopamine monomers to construct zwitterionic nanogels and chelate copper ions with phenolic hydroxyl groups for synergistic tumor therapy.
[0007] Therefore, developing a copper ion-chelated zwitterionic polymer nanogel and applying it to CDT / chemotherapy synergistic tumor treatment has significant clinical value and broad application prospects. Summary of the Invention
[0008] To address the shortcomings of existing iron-based nanozymes in tumor microenvironment, such as insufficient catalytic activity and limited GSH consumption capacity, and the lack of efficient delivery carriers in existing copper-based nanoparticles, which hinders the implementation of CDT / chemotherapy synergistic therapy, this invention provides a copper-chelated zwitterionic polymer nanogel and its applications. This invention constructs a zwitterionic nanogel framework containing a catechol structure, utilizing the phenolic hydroxyl groups and Cu... 2+ The dynamic coordination mechanism enables efficient chelation of copper ions and responsive release in the tumor microenvironment. Combined with the reducible degradation properties of the disulfide bond cross-linking network, multiple regulation of copper ion delivery stability, GSH consumption capacity, and synergistic drug release is achieved. At the same time, the use of precipitation polymerization and coordination chelation methods significantly improves the copper loading efficiency, colloidal stability, and anti-tumor effect of the nanogel.
[0009] This invention first provides a copper ion-chelated zwitterionic polymer nanogel. This nanogel is a cross-linked copolymer, its backbone consisting of zwitterionic monomer units, monomer units containing catechol groups, and cross-linking agent units containing disulfide bonds. Specifically, the zwitterionic monomer is 2-methacryloyloxyethylphosphorylcholine (MPC), the catechol-containing monomer is dopamine methacrylamide (DMA), and the disulfide-containing cross-linking agent is N,N'-bis(acryloyl)cysteine (BAC). This nanogel binds to copper ions (Cu ions) through the phenolic hydroxyl groups on the catechol-containing monomer units. 2+ It undergoes coordination, thereby chelating copper ions.
[0010] In the nanogel of the present invention, the monomer units derived from dopamine methacrylamide account for 10% to 70% of the total monomer units by mass. In some embodiments, this proportion is 20%, 30%, 40%, 50%, or 60%. Experiments show that when the DMA content is 50%, the nanogel has a particle size of 263.52 nm, a polydispersity index (PDI) of 0.007, and a zeta potential of -7.08 mV, exhibiting optimal particle size uniformity and dispersion stability. Overall, the nanogel has a particle size of 200–310 nm, a polydispersity index ≤0.22, and a zeta potential of -2.95 to -11.6 mV.
[0011] In this invention, when the mass ratio of copper chloride to nanogel is 1:10 to 1:5, the corresponding copper loading rate is 4.12% to 8.54%. Preferably, the mass ratio of copper chloride to nanogel is 1:8, at which point the copper loading rate is 5.26%, the nanogel particle size is 271.71 nm, the PDI is 0.024, and it shows low toxicity to normal cells in cytotoxicity experiments.
[0012] Furthermore, the nanogel described in this invention can also be loaded with the antitumor drug doxorubicin (DOX). In some embodiments, the mass ratio of nanogel to doxorubicin is 10:1, the drug loading can reach 5.06%, and the encapsulation efficiency is 53.3%. The nanogel loaded with doxorubicin can achieve synergistic delivery of chemotherapy and chemokinetic therapy (CDT).
[0013] This invention also provides a method for preparing the above-mentioned copper ion-chelated zwitterionic polymer nanogel. This method includes the following two core steps: The first step involved preparing P(MPC-ss-DMA) nanogels. 2-Methacryloxyethylphosphorylcholine (MPC), dopamine methacrylamide (DMA), N,N'-bis(acryloyl)cysteine (BAC), and azobisisobutyronitrile (AIBN) were dissolved in acetonitrile and ultrasonically dispersed until no particles remained. After introducing an inert gas, the temperature was raised to 80–100°C, and the mixture was refluxed for precipitation polymerization for 30–60 minutes. After cooling, the mixture was centrifuged, washed with water, and freeze-dried to obtain a white powdery P(MPC-ss-DMA) nanogel. The amounts of MPC, DMA, BAC, and AIBN were 60–200 mg, 0–140 mg, 20–80 mg, and 20–60 mL, respectively. Preferably, the reaction temperature was 90°C, the reaction time was 40 minutes, and the mass ratio of MPC, DMA, and BAC was 100:100:40.
[0014] The second step is the chelation of copper ions. The above-mentioned P(MPC-ss-DMA) nanogel is dispersed in a buffer solution with a pH of 8–10 (concentration 3–6 mg / mL). A CuCl2 solution of 0.05–0.20 mol / L is added at a CuCl2 to nanogel mass ratio of 1:10–1:3. The mixture is stirred at room temperature for 2–6 hours to allow the CuCl2 to chelate. 2+ The DMA nanogel undergoes coordination with the phenolic hydroxyl groups of the DMA units. After the reaction, the mixture is centrifuged, washed with water, and freeze-dried to obtain a brownish-yellow powdery P(MPC-ss-DMA)@Cu nanogel. Preferably, the buffer solution is a pH 9 buffer solution, the mass ratio of CuCl2 to nanogel is 1:8, and the stirring time is 4 hours.
[0015] This invention further provides a method for preparing a copper-chelated zwitterionic polymer nanogel loaded with doxorubicin. Based on the above two-step preparation method, this method further includes a third step: mixing the prepared P(MPC-ss-DMA)@Cu nanogel with doxorubicin, mixing under light-protected conditions for 18–48 hours, centrifuging and washing to obtain the doxorubicin-loaded nanogel P(MPC-ss-DMA)@Cu-DOX. In some embodiments, the mass ratio of nanogel to doxorubicin is 10:1, the mixing time under light-protected conditions is 24 hours, and the mixing method is rotary mixing in a suspension apparatus or magnetic stirring (100–300 rpm). A dilute NaOH aqueous solution can be added to adjust the pH to weakly alkaline to improve the loading efficiency of doxorubicin.
[0016] This invention also relates to the use of the aforementioned copper-chelated zwitterionic polymer nanogels (including unloaded and drug-loaded formulations) in the preparation of medicaments for treating tumors. The tumor is preferably colon cancer, but can also be liver cancer, gastric cancer, or breast cancer. In application, the medicament can be administered to mice via intravenous injection. For unloaded copper-chelated zwitterionic polymer nanogels, the Cu dosage is equal to the DOX dosage (3–6 mg / kg). For drug-loaded copper-chelated zwitterionic polymer nanogels, the Cu dosage is equal to the DOX dosage, and the total dosage is 3–6 mg / kg (based on DOX).
[0017] The medication is administered once every 3 days, for a total of 4 doses.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. Innovative Material Design and Coordination Mechanism: This invention is the first to introduce a dopamine monomer containing catechol groups into the P(MPC-ss-DMA) zwitterionic nanogel framework, through the interaction of phenolic hydroxyl groups and Cu... 2+The dynamic coordination mechanism enables efficient chelation of copper ions. This coordination method is mild and dynamically reversible, avoiding the damage to the nanogel structure caused by covalent modification, and is pH-dependent (stable chelation under physiological neutral pH conditions and responsive dissociation in weakly acidic tumor microenvironment), providing a new strategy for the construction of copper-based CDT nanoformulations.
[0019] 2. Controllable process and good reproducibility: This invention uses precipitation polymerization to prepare nanogels without the need for surfactants. The resulting nanogels have uniform particle size (PDI<0.1) and clean surface. The copper loading rate (4.12%~8.54%) can be precisely controlled by adjusting the mass ratio of CuCl2 to nanogels (1:10~1:5). The process parameters are clear, the batch-to-batch differences are small, and it has good prospects for industrial application.
[0020] 3. Excellent Multi-Response to Tumor Microenvironment: The nanogel of this invention constructs a three-dimensional cross-linked network with disulfide bonds, endowing the material with responsive degradation characteristics in the high-concentration GSH microenvironment of the tumor. Simultaneously, the copper ions chelated by the gel can undergo a reversible Cu²⁺ / Cu⁺ redox cycle, and the reduction of Cu²⁺ by intracellular GSH can further consume endogenous GSH. The system relies on a dual pathway of gel disulfide bond reduction and cleavage and copper ion reduction to consume intracellular GSH, and on Cu⁺-mediated Fenton-like reactions to continuously generate hydroxyl radicals, constructing a dual oxidative stress enhancement mechanism of "GSH depletion synergistically generating large amounts of reactive oxygen species." This effectively relieves the antagonistic effect of the high-concentration GSH microenvironment of the tumor on CDT reactive oxygen species scavenging, enhances the level of intracellular oxidative stress in the tumor, and strengthens the therapeutic effect of chemokinetics.
[0021] 4. Excellent biocompatibility and long-term circulation stability: Cytotoxicity experiments showed that the 48-h survival rate of P(MPC-ss-DMA) nanogels against normal LO2 cells and tumor cells CT26 was >92% (concentration 200 μg / mL), exhibiting extremely low cytotoxicity. The zwitterionic surface endowed the nanogels with excellent resistance to non-specific protein adsorption. The particle size of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu did not change significantly within 30 days in PBS 7.4 buffer solution and PBS 7.4 buffer solution containing bovine serum albumin (BSA), demonstrating excellent colloidal stability, which is beneficial for long-term circulation in vivo and passive tumor targeting.
[0022] 5. Significant synergistic antitumor effect of CDT / chemotherapy: The present invention, after loading doxorubicin, forms the P(MPC-ss-DMA)@Cu-DOX drug delivery system. In vitro cell experiments showed that the inhibition rate reached 45% at a concentration of 1.0 μg / mL, which was higher than the sum of CDT alone (P(MPC-ss-DMA)@Cu) and chemotherapy alone (P(MPC-ss-DMA)@DOX) (37%), and the inhibition rate reached 87% at a concentration of 10.0 μg / mL. In vivo tumor inhibition experiments showed that the tumor inhibition rate of the P(MPC-ss-DMA)@Cu-DOX group reached 86.5%, which was significantly better than the free DOX group (54.1%), P(MPC-ss-DMA)@Cu (58.9%) and P(MPC-ss-DMA)@DOX (75.9%).
[0023] In summary, this invention provides a novel copper ion chelate zwitterionic polymer nanogel with excellent performance and significant synergistic anti-tumor effect of CDT / chemotherapy. It can be used alone for CDT treatment or in combination with chemotherapeutic drugs to achieve synergistic anti-tumor effect, providing a new platform technology for the development of tumor microenvironment-responsive nanomedicines. Attached Figure Description
[0024] Figure 1 The infrared spectrum of P(MPC-ss-DMA) nanogels.
[0025] Figure 2 Transmission electron microscopy (TEM) images (scale bar 500 nm) of P(MPC-ss-DMA) nanogels with different DMA contents. The DMA contents are: 10% (a), 20% (b), 30% (c), 40% (d), 50% (e), and 60% (f).
[0026] Figure 3 XPS full spectrum (a) and Cu2p spectrum (b) of P(MPC-ss-DMA)@Cu nanogel.
[0027] Figure 4 TEM image (scale bar 200 nm) of P(MPC-ss-DMA)@Cu nanogel with a CuCl2 to nanogel mass ratio of 1:8.
[0028] Figure 5 The 24-h cytotoxicity of P(MPC-ss-DMA)@Cu nanogels prepared with different CuCl2 to nanogel mass ratios to normal LO2 cells.
[0029] Figure 6 The results show the 48-h cytotoxicity of P(MPC-ss-DMA) nanogel against normal cells LO2(a) and tumor cells CT26(b).
[0030] Figure 7 The results show the stability of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu nanogels in PBS 7.4 buffer and PBS 7.4 buffer containing BSA.
[0031] Figure 8 The reduction degradation curve (a) and molecular weight diagram (b) of P(MPC-ss-DMA) nanogel are shown.
[0032] Figure 9 The results show the in vitro GSH scavenging ability of P(MPC-ss-DMA)@Cu nanogel.
[0033] Figure 10 EPR spectra of ·OH generated under different reaction conditions (a) and the effect of P(MPC-ss-DMA)@Cu nanogel on the degradation of methylene blue (MB) under different conditions (bd).
[0034] Figure 11 Results of 24-h cytotoxicity of P(MPC-ss-DMA)@Cu nanogel on CT26 cells before and after the addition of copper inhibitor.
[0035] Figure 12 This is a dose-response graph showing the change in cell survival rate with concentration in each experimental group.
[0036] Figure 13 The curves showing the change in tumor volume over time in mice during the treatment process in each experimental group (n=5) are shown. Data are expressed as mean ± standard deviation (Mean ± SD); p>0.05 indicates no statistical difference (ns); p<0.05 indicates a significant difference (*); p<0.01 indicates a highly significant difference (**); p<0.001 indicates an extremely significant difference (***).
[0037] Figure 14 A bar chart showing the weight of tumors removed from mice in each experimental group after treatment.
[0038] Figure 15 The figures show the changes in body weight over time in each experimental group of mice during treatment (n=5). Data are expressed as mean ± standard deviation (Mean ± SD); p>0.05 indicates no statistical difference (ns); p<0.05 indicates a significant difference (*); p<0.01 indicates a highly significant difference (**); p<0.001 indicates an extremely significant difference (***). Detailed Implementation
[0039] To make the technical solution of this invention clearer and more complete, to facilitate understanding and implementation by those skilled in the art, and to fully support the protection scope defined by the claims, the technical solution of this invention will be described in detail below in conjunction with specific preparation, characterization, performance testing and in vitro and in vivo experimental methods.
[0040] In the specific implementation section of this invention, the following contents are described in sequence from material synthesis to functional verification: preparation and structural characterization of zwitterionic nanogels (1), preparation and structural characterization of copper ion chelate nanogels (2), determination method of copper ion content in copper ion chelate nanogels (3), cytotoxicity assessment of nanogels and copper ion chelate nanogels (4), stability test of nanogels and copper ion chelate nanogels (5), reductive degradation test of nanogels (6), in vitro GSH scavenging ability test of copper ion chelate nanogels (7), in vitro free radical generation ability test of copper ion chelate nanogels (8), method of loading antitumor drugs onto nanogels and copper ion chelate nanogels (9), toxicity of copper ion chelate nanogels to tumor cells (10), synergistic antitumor effect of copper ion chelate drug-loaded nanogels in vitro (11), and in vivo antitumor effect assessment of copper ion chelate drug-loaded nanogels (12).
[0041] (1) Preparation and structural characterization of P(MPC-ss-DMA) nanogels In a 100 mL three-necked flask equipped with a spherical condenser and mechanical stirrer, 60–200 mg of monomer MPC, 0–140 mg of monomer DMA, 20–80 mg of crosslinking agent BAC, and 2–6 mg of initiator AIBN were weighed. 20–60 mL of acetonitrile was added, and the mixture was sonicated until no particles remained. After purging with N2 for 20–40 min, the temperature was raised to 80–100 °C, and the reaction was carried out for 30–60 min. The mixture was then cooled to room temperature, centrifuged at 10,000–12,000 rpm for 10–15 min, washed with water, and centrifuged 2–3 times to obtain purified P(MPC-ss-DMA) nanogel. After vacuum freeze-drying for 2–5 days, a white powdery solid was obtained. The chemical structure of the synthesized P(MPC-ss-DMA) nanogel was analyzed by infrared spectroscopy, its morphology was observed by transmission electron microscopy (TEM), and its potential, particle size, and monodispersity were determined by dynamic light scattering (DLS).
[0042] (2) Preparation and structural characterization of P(MPC-ss-DMA)@Cu nanogels 6–30 mg of P(MPC-ss-DMA) nanogel was dispersed in 2–5 mL of pH 8–10 buffer solution to achieve a concentration of 3–6 mg / mL. Following a CuCl2 to nanogel mass ratio of 1:10–1:3, an appropriate volume of 0.05–0.20 mol / L CuCl2 solution was added, along with 1–3 mL of pH 8–10 buffer solution. After uniform dispersion, the mixture was stirred at room temperature for 2–6 h. After the reaction was complete, the mixture was centrifuged at 10,000–12,000 rpm, washed 2–3 times with water, and then freeze-dried to obtain a brownish-yellow powder. The chemical structure of P(MPC-ss-DMA)@Cu was analyzed using X-ray photoelectron spectroscopy (XPS), its morphology was observed using transmission electron microscopy (TEM), and its particle size and monodispersity were determined using dynamic light scattering (DLS).
[0043] (3) Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) was used to determine the copper ion content in the nanogel. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used to quantitatively determine the copper content in the nanogel samples. The copper content in the nanogel samples was calculated by measuring the copper ion content in the supernatant obtained by centrifugation during the preparation of P(MPC-ss-DMA)@Cu nanogels.
[0044] (4) Cytotoxicity test of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu nanogel Cytotoxicity was determined using the CCK-8 assay. The biocompatibility of P(MPC-ss-DMA) with P(MPC-ss-DMA)@Cu nanogel was evaluated using normal human hepatocytes (LO2 cells) and colon cancer cells (CT26 cells). The cell culture methods and specific procedures are as follows: cells were digested, counted, and prepared to a concentration of 1×10⁻⁶. 4 ~1×10 5 Cells were cultured at 37 °C for 24 h in a 5% CO2 incubator. 50–200 μL of cell suspension was added to each well of a 96-well cell culture plate. The plate was then incubated for 24 h. Working solutions containing 0–200 μg / mL P(MPC-ss-DMA) nanogels and 2–14 μg / mL P(MPC-ss-DMA)@Cu nanogels were prepared using complete culture medium (80–90% RPMI 1640 medium + 10–20% fetal bovine serum). 50–200 μL of the corresponding working solution was added to each well, with three replicates for each concentration. Cells were cultured at 37 °C for 24–48 h in a 5% CO2 incubator, and the supernatant was discarded. The 96-well plate was stained with CCK-8, and the OD value was measured at λ=450 nm.
[0045] (5) Stability experiment of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu nanogels The long-term circulation stability of the nanogels was investigated under simulated in vivo blood circulation conditions (pH 7.4). P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu were dispersed at concentrations of 0.25–1.0 mg / mL in 0.01–0.02 M PBS 7.4 buffer and PBS 7.4 buffer with bovine serum albumin (BSA) concentrations of 0.5–2.0 mg / mL. The particle size changes of the nanogels at different time intervals over 30 days were monitored by DLS.
[0046] (6) Reductive degradation experiment of P(MPC-ss-DMA) nanogel P(MPC-ss-DMA) nanogels were dispersed in 0.01–0.02 M PBS pH 7.4 buffer solutions with GSH concentrations ranging from 0 to 20 mM, to achieve a concentration of 0.5–1.0 mg / mL, and degradation experiments were conducted at 37 °C. The molecular weight of the degraded nanogels was determined by gel permeation chromatography (GPC). Changes in scattered light intensity were tracked using dynamic light scattering (DLS) to investigate its redox degradation performance. The test temperature was set at 37 °C, and the scattered light intensity of the samples was recorded at set time points. The ratio of the scattered light intensity of the sample at different time points to that of the initial sample was defined as the relative turbidity of the sample; changes in the relative turbidity reflected the degree of degradation.
[0047] (7) In vitro GSH scavenging ability of P(MPC-ss-DMA)@Cu nanogel To simulate a tumor cell environment, the consumption of GSH was assessed using a colorimetric reaction between GSH and 5,5′-dithiobis(2-nitrobenzoic acid) (DTNB). The specific procedures were as follows: 0.05–0.1 mM aqueous solutions of GSH and DTNB were prepared. 0.5–2.0 mL of each solution were reacted with DTNB for 10–30 min, and then the spectra were scanned using a UV-Vis spectrophotometer in the 200–800 nm range to observe the maximum absorption wavelength.
[0048] GSH was dissolved in water, pH 5.5, and pH 7.4 buffer solutions to achieve a final concentration of 0.1–0.5 mM. 0.5–2 mg of P(MPC-ss-DMA)@Cu nanogel was weighed and added to 1–3 mL of GSH solutions (including aqueous solutions) at different pH values. The solutions were ultrasonically dispersed and incubated at 37 °C for 10–30 min, followed by centrifugation at 8000–12000 rpm for 8–15 min. 0.1–0.5 mL of the supernatant was taken from each solution and added to 1.0–2.0 mL of pH 8 buffer solution. Then, 0.1–0.5 mL of 0.1–0.5 mM DTNB aqueous solution was added to each solution. After incubation for 10–30 min, UV-Vis spectrophotometry was performed in the 200–800 nm range, and the absorbance at 409 nm was observed.
[0049] (8) In vitro free radical generation ability of copper ion chelating nanogels The ability of copper ion chelate nanogels to generate free radicals was detected by electron paramagnetic resonance (EPR) spectroscopy using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO). The specific procedure was as follows: 0.05–0.2 mL of 0.5–2 mg / mL chelate nanogel, 0.05–0.2 mL of 10–30 mM H₂O₂, 0–0.2 mL of 1–5 mM GSH, and 0–50 μL of 50–150 mM DMPO₂ were added to 1.5–2.0 mL of PBS buffer (0.01–0.02 M, pH 7.4). The reaction was allowed to proceed for 10–30 min at room temperature before measurement.
[0050] Methylene blue (MB) can be degraded by hydroxyl radicals (⋅OH). The degradation of MB was measured by monitoring changes in UV-Vis absorbance at 664 nm, thus evaluating the ability of P(MPC-ss-DMA)@Cu nanogels to generate ⋅OH. The specific experimental steps were as follows: P(MPC-ss-DMA)@Cu nanogels (30–60 μg / mL) were dispersed in a mixture containing GSH (0.1–0.3 mM), H₂O₂ (1–3 mM), and MB (0.005–0.02 mM). The reaction was carried out at room temperature for a predetermined time. The reaction mixture was then centrifuged at 8000–12000 rpm for 3–8 min, and the absorption spectrum of the supernatant was measured using a UV-Vis spectrophotometer in the wavelength range of 500–800 nm. Furthermore, the effect of temperature on MB degradation was investigated by conducting the reaction at different temperatures ranging from 20 °C to 60 °C.
[0051] (9) Drug loading experiments of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu nanogels Doxorubicin (DOX), a first-line clinical oncology drug, was selected as the model drug. 5–10 mg of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu nanogels were dispersed in 1–2 mL of pure water, respectively. 1–4 mg of DOX was dissolved in 1–4 mL of aqueous solution. The solutions were mixed and ultrasonically dispersed until homogeneous. The mixture was then adjusted to a weakly alkaline state using 0.1 M dilute NaOH aqueous solution and ultrasonically dispersed again. The mixture was placed in a suspension apparatus or magnetically stirred (100–300 rpm) at room temperature in the dark for 18–48 h. The DOX-loaded nanogels were collected by centrifugation and washed 2–3 times with pure water to remove surface-adsorbed DOX.
[0052] (10) P(MPC-ss-DMA)@Cu nanogel tumor cell toxicity experiment Using colon cancer cells (CT26) as the research subject, the CCK-8 assay was used to compare and analyze Cu. 2+ The difference in cytotoxicity of chelated nanogels to tumor cells before and after the addition of a copper inhibitor was investigated to evaluate the material's effect on cell proliferation. The specific procedures were as follows: First, cells were digested, counted, and prepared to a concentration of 6 × 10⁻⁶. 4 ~1×10 5 Cell suspension of cells / mL, in 50-200 μL (6 × 10⁻⁶) per well. 3 ~1×10 4 Cells were seeded in 96-well plates and incubated overnight at 37°C with 5% CO2 to allow cell adhesion. After cell adhesion, test working solutions containing different concentrations of the material were prepared using complete culture medium (80%–90% DMEM + 10%–20% fetal bovine serum). Before material treatment, 10–20 μM ammonium tetrathiomolybdate (ATTM) solution was added to the corresponding wells and pretreated at 37°C for 2–6 h. Subsequently, 100–200 μL of the corresponding concentration of the material working solution was added to each well, with 3–4 replicates per concentration. Cells were then cultured at 37°C with 5% CO2 for 24 h. After culture, the supernatant was discarded, and the 96-well plates were stained with CCK-8 to measure the OD value (λ = 450 nm), and the cell proliferation rate was calculated accordingly.
[0053] (11) Synergistic anti-tumor effect of P(MPC-ss-DMA)@Cu-DOX nanogel in vitro The ability of free DOX, P(MPC-ss-DMA)@DOX, P(MPC-ss-DMA)@Cu, and P(MPC-ss-DMA)@Cu-DOX nanogels to kill tumor cells was evaluated in colon cancer cells (CT26). The cell culture methods and specific procedures are as follows: cells were digested, counted, and prepared to a concentration of 1×10⁻⁶. 4 ~1×10 5 Cell suspension was prepared at 100-200 μL / mL, and added to each well of a 96-well cell culture plate. The cell culture plate was then incubated at 37 ℃ in a 5% CO2 incubator for 24 h. Working solutions of 0.5-10 μg / mL free DOX, P(MPC-ss-DMA)@DOX nanogels with equal DOX concentration, P(MPC-ss-DMA)@Cu nanogels with equal Cu and DOX concentrations, and P(MPC-ss-DMA)@Cu-DOX nanogels with equal DOX and Cu concentrations (the sum of DOX and Cu concentrations equals the free DOX concentration) were prepared using complete culture medium (80-90% DMEM + 10-20% fetal bovine serum). 50-200 μL of the corresponding working solution was added to each well, with 3-4 replicates for each concentration. Cells were then cultured at 37 ℃ in a 5% CO2 incubator for 48 hours. After h, discard the supernatant; stain the 96-well plate with CCK-8 and measure the OD value at λ=450 nm. Calculate the cell viability (Viability %) and inhibition rate (Fa, inhibition rate = 1 - viability %).
[0054] (12) In vivo tumor-suppressing effect of P(MPC-ss-DMA)@Cu-DOX nanogel 4×10 6 ~8×10 6 CT26 cells (dispersed in 50–100 μL PBS) were subcutaneously injected into the left axilla of each male Balb / c mouse to establish a CT26 tumor-bearing mouse model. The CT26 tumor-bearing mice were randomly divided into six groups (n=5 per group). Tumor volume was calculated using the following formula: Tumor volume = 0.5 × length × width 2 When the tumor volume reaches 90-120 mm 3At that time, the six groups were given the following treatments: (1) PBS control group; (2) P(MPC-ss-DMA) (80~120 mg / kg); (3) P(MPC-ss-DMA)@Cu (equivalent Cu dose of 3~8 mg / kg, the same as free DOX dose); (4) free DOX (3~8 mg / kg); (5) P(MPC-ss-DMA)@DOX (equivalent DOX dose of 3~8 mg / kg, the same as free DOX dose); (6) P(MPC-ss-DMA)@Cu-DOX (equivalent (Cu dose + DOX dose) of 3~8 mg / kg, the same as free DOX dose, and Cu dose = DOX dose). Each group was injected into the body via tail vein on days 0, 3, 6 and 9. Mice were weighed and had tumor volume measured every other day. On day 14, mice in each group were sacrificed according to animal ethics, and their major organs (heart, liver, spleen, lungs, and kidneys) and tumors were removed, fixed with 4% paraformaldehyde, and the mass of the tumors was measured. Data are expressed as Mean ± SD (n = 5): p > 0.05 indicates no statistical difference (ns); p < 0.05 indicates significant difference (*); p < 0.01 indicates highly significant difference (**); p < 0.001 indicates extremely significant difference (***).
[0055] The methods described in (1) to (12) above cover the complete technical chain from the chemical synthesis of nanogels, physicochemical characterization, in vitro functional verification to in vivo pharmacodynamic evaluation. These methods, on the one hand, fully disclose the technical solution of this invention, ensuring that those skilled in the art can replicate this invention without creative effort; on the other hand, the experimental data obtained by each method (such as particle size, potential, copper loading rate, GSH consumption rate, free radical generation capacity, cell survival rate, tumor inhibition rate, etc.) provide direct support and verification for the structural features, composition ratios, performance parameters, and application effects in the claims. The specific parameters, reaction conditions, testing methods, and result examples described below are all preferred embodiments of this invention, but are not intended to limit the scope of protection. Equivalent substitutions, modifications, or optimizations made by those skilled in the art based on the technical concept of this invention are all within the scope of protection of this invention.
[0056] Example 1 Preparation and characterization of P(MPC-ss-DMA) nanogels I. Preparation Method In a 100 mL three-necked flask equipped with a spherical condenser and mechanical stirrer, 100 mg of monomer MPC, 100 mg of monomer DMA, 40 mg of crosslinking agent BAC, and 4 mg of initiator AIBN were weighed out. 40 mL of acetonitrile was added, and the mixture was sonicated until no particles remained. After purging with N2 for 30 min, the temperature was raised to 90 °C, and the reaction was carried out for 40 min. The mixture was then cooled to room temperature, centrifuged at 12000 rpm for 10 min, washed with water, and centrifuged three times to obtain purified P(MPC-ss-DMA) nanogel. After vacuum freeze-drying for 3 days, a white powdery solid was obtained.
[0057] II. Structural Characterization The structure of P(MPC-ss-DMA) nanogels was analyzed using Fourier transform infrared spectroscopy (FTIR). Figure 1 As shown, the broad and strong absorption peak at 3400–3200 cm⁻¹ is attributed to the overlapping stretching vibration of the associated phenolic hydroxyl group and the secondary amide NH in dopamine methacrylamide; 1615 cm⁻¹ -1 and 1511 cm -1 The absorption peak at 1127 cm⁻¹ is mainly due to the C=C skeletal vibration of the dopamine benzene ring (where 1615 cm⁻¹ is superimposed with the C=O stretching vibration of the amide I band of the secondary amide, and 1511 cm⁻¹ is superimposed with the in-plane bending vibration of the NH group of the amide II band of the secondary amide); -1 The absorption peak at 1036 cm⁻¹ corresponds to the COC asymmetric stretching vibration of the ester group in MPC; -1 The absorption peak at that point is attributed to the stretching vibration of the POC bond in the MPC phosphorocholine group.
[0058] III. Particle Size and Electric Potential The particle size, particle size distribution, and potential of P(MPC-ss-DMA) nanogels prepared with different DMA contents were determined by dynamic light scattering (DLS), and the results are shown in Table 1. Table 1 shows that as the DMA content increased from 0% to 70%, the particle size of the nanogels increased from 214.68 nm to 300.57 nm, and the potential increased from -0.52 mV to -11.60 mV. When the DMA content was greater than 50%, the polydispersity index (PDI) was greater than 0.1, indicating a decrease in the uniformity of the nanogel particle size distribution. Considering all factors, the nanogel P(MPC-ss-DMA-50) with a DMA content of 50% was selected as the subject of subsequent research.
[0059] Table 1. Particle size, particle size distribution, and potential of P(MPC-ss-DMA) nanogels with different DMA contents. a. The percentage of DMA in the monomer.
[0060] b. Polydispersity index is used to characterize the distribution of particle size.
[0061] IV. Morphological Observation The morphology and dispersibility of P(MPC-ss-DMA) nanogels were observed by transmission electron microscopy (TEM), and the results are as follows: Figure 2 As shown. From Figure 2 It can be seen that the nanogels have a regular spherical morphology and good dispersibility and uniformity. When the DMA content increases from 10% to 60%, the particle size changes from about 110 nm to about 190 nm, which is the same trend as that of DLS. The particle size of the nanogels observed under electron microscopy is smaller than the hydrated particle size determined by dynamic light scattering because the electron microscopy observation and measurement were carried out under high vacuum and dry conditions, and the gel network was in a state of shrinkage and collapse; while dynamic light scattering was measured in an aqueous solution, where the nanogels were in a fully hydrated and swollen state.
[0062] Example 2 Preparation, characterization and copper loading rate determination of P(MPC-ss-DMA)@Cu nanogels I. Preparation Method 10 mg of P(MPC-ss-DMA-50) nanogel was dispersed in 2 mL of pH 9 buffer solution to a concentration of 5 mg / mL. 0.1 mol / L CuCl2 solution was added according to the CuCl2 to nanogel mass ratios of 1:10, 1:8, 1:5, and 1:3, followed by 1 mL of pH 9 buffer solution. After uniform dispersion, the mixture was stirred at room temperature for 4 h. After the reaction was complete, the mixture was centrifuged at 12000 rpm, washed three times with water, and then freeze-dried to obtain a brownish-yellow powder.
[0063] II. Structural Characterization The chemical structure of P(MPC-ss-DMA-50)@Cu was analyzed by X-ray photoelectron spectroscopy (XPS), and the results are as follows: Figure 3 As shown. XPS results indicate that P(MPC-ss-DMA)@Cu nanogel contains elements such as C, N, P, O, and Cu. Figure 3 a). Cu2p XPS spectrum ( Figure 3b) indicates that both Cu²⁺ and Cu⁺ valence states exist simultaneously in the sample: characteristic peaks at 934.86 eV (Cu 2p3 / 2) and 954.75 eV (Cu 2p1 / 2), and typical satellite peaks at 943.70 eV, 962.23 eV, 941.20 eV, and 961.75 eV confirm the presence of Cu²⁺; at the same time, characteristic peaks at 932.82 eV (Cu 2p3 / 2) and 952.80 eV (Cu 2p1 / 2) confirm the presence of Cu⁺.
[0064] III. Particle size, morphology and copper loading The particle size and distribution of P(MPC-ss-DMA)@Cu nanogels prepared with different mass ratios of P(MPC-ss-DMA) to CuCl2 were determined by dynamic light scattering (DLS), and the copper loading was determined by ICP-OES. The results are shown in Table 2. Table 2 shows that after P(MPC-ss-DMA) chelates with CuCl2, the particle size of the chelated copper nanogel changes from 263.52 nm before chelation to 265.24 nm (10:1), 271.71 nm (8:1), and 275.62 nm (5:1) with varying mass ratios of P(MPC-ss-DMA) to CuCl2, while maintaining good dispersibility (PDI < 0.1). Furthermore, the copper loading increases from 4.12% (10:1) to 5.26% (8:1) and 8.54% (5:1). When the mass ratio is 3:1, the nanogel is unstable and precipitation occurs. The morphology of P(MPC-ss-DMA)@Cu-8 was observed by transmission electron microscopy (TEM), such as... Figure 4 As shown. From Figure 4 It can be seen that P(MPC-ss-DMA)@Cu-8 has a regular spherical morphology with a particle size of about 170 nm. Compared with the unchelated P(MPC-ss-DMA) nanogel, the surface of the microspheres is relatively rough and the particle size is slightly larger, indicating that Cu²⁺ has coordinated with the phenolic hydroxyl groups from dopamine.
[0065] Table 2. Particle size, distribution, and copper loading of P(MPC-ss-DMA)@Cu nanogels prepared with different mass ratios of P(MPC-ss-DMA) nanogels to CuCl2. a. Nanogel P (MPC-ss-DMA) with 50% DMA content.
[0066] b The mass ratio of P(MPC-ss-DMA) to CuCl2.
[0067] c.Polydispersity index is used to characterize the distribution of particle size.
[0068] IV. Determination of Copper Ion Content (ICP-OES) The copper content in the nanogel samples was determined using inductively coupled plasma optical emission spectrometry (ICP-OES). Specifically, the supernatant obtained during the preparation of P(MPC-ss-DMA)@Cu nanogels was collected by centrifugation, appropriately diluted with deionized water, and the concentration of copper ions in the supernatant was determined by ICP-OES. The chelated copper content in the nanogel samples was calculated by subtracting the residual copper in the supernatant from the total amount of copper added, and expressed as a percentage (%). The results are shown in Table 2 above.
[0069] Example 3 Biocompatibility, stability and reductive degradation of nanogels I. Cytotoxicity Experiment Cytotoxicity was determined using the CCK-8 assay. The biocompatibility of P(MPC-ss-DMA) with P(MPC-ss-DMA)@Cu nanogel was evaluated using normal human hepatocytes (LO2 cells) and colon cancer cells (CT26 cells). Cells were digested, counted, and prepared into a concentration of 8 × 10⁻⁶. 4 Add 100 μL of cell suspension per well (8 × 10⁶ cells / mL) to each well of a 96-well cell culture plate. 3 Cell culture plates were incubated at 37 ℃ in a 5% CO2 incubator for 24 h. Working solutions containing 0–200 μg / mL P(MPC-ss-DMA) nanogels and 2–14 μg / mL P(MPC-ss-DMA)@Cu nanogels were prepared using complete culture medium (90% RPMI 1640 medium + 10% fetal bovine serum). 100 μL of the corresponding working solution was added to each well, with three replicates for each concentration. For P(MPC-ss-DMA) nanogels, LO2 and CT26 cells were cultured at 37 ℃ in a 5% CO2 incubator for 48 h, respectively. For P(MPC-ss-DMA)@Cu nanogels, LO2 cells were cultured for 24 h, after which the supernatant was discarded. The 96-well plates were stained with CCK-8, and the OD value was measured at λ=450 nm.
[0070] The 24-h cytotoxicity results of P(MPC-ss-DMA)@Cu nanogels prepared with different mass ratios of P(MPC-ss-DMA) nanogels to CuCl2 on normal cells (LO2) are as follows: Figure 5As shown in the figure, the results indicate that the cytotoxicity of the nanogel increases with the increase of CuCl2 content. When the mass ratio of P(MPC-ss-DMA) nanogel to CuCl2 is 10:1 and 8:1, the nanogel exhibits lower cytotoxicity, while a mass ratio of 5:1 shows higher cytotoxicity. Considering that nanogels, as drug carriers, need to have a certain copper loading capacity and good biocompatibility, the nanogel prepared with a mass ratio of P(MPC-ss-DMA) nanogel to CuCl2 of 8:1 was chosen as the subject of subsequent research.
[0071] Furthermore, the 48-hour cytotoxicity of P(MPC-ss-DMA) nanogel against normal LO2 cells and CT26 colon cancer cells was as follows: Figure 6 As shown in (a) and (b), P(MPC-ss-DMA) nanogels exhibited extremely low cytotoxicity to both cell types, with cell viability >92% at all concentrations, indicating that P(MPC-ss-DMA) nanogels have excellent biocompatibility as a drug carrier.
[0072] II. Stability Test The long-term circulation stability of the nanogels was investigated under simulated in vivo blood circulation conditions (pH 7.4). P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu were dispersed at a concentration of 0.5 mg / mL in 0.01 M PBS 7.4 buffer and 0.01 M PBS 7.4 buffer with a bovine serum albumin (BSA) concentration of 1 mg / mL, respectively. The particle size changes of the nanogels at different time intervals over 30 days were monitored using DLS. The results are as follows: Figure 7 As shown, the particle size of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu nanogels did not change significantly within 30 days, indicating that both have good stability.
[0073] III. Reduction and Degradation Experiment P(MPC-ss-DMA) nanogels were dispersed in 0.01 M PBS pH 7.4 buffer solution with a GSH concentration of 10 mM to achieve a concentration of 0.5 mg / mL, and degradation experiments were conducted at 37 ℃. The molecular weight of the degraded nanogels was determined by gel permeation chromatography (GPC). Changes in scattered light intensity were tracked using dynamic light scattering (DLS) to investigate its redox degradation performance. The test temperature was set at 37 ℃, and the scattered light intensity of the samples was recorded at set time points. The ratio of the scattered light intensity of the sample at different time points to that of the initial sample was defined as the relative turbidity of the sample; changes in the relative turbidity reflected the degree of degradation.
[0074] The results are as follows Figure 8 As shown. From Figure 8 It can be seen that in a 10 mM GSH PBS 7.4 buffer solution, the relative turbidity of the P(MPC-ss-DMA) nanogel decreased with time, reaching approximately 20% after 8 h. The molecular weight of the degraded nanogel, determined by GPC, was M... w It is 2309 g / mol, M n The value was 2118 g / mol, indicating that the disulfide bonds at the cross-linking points inside the nanogel could be reduced to thiol groups by GSH and degraded, with the degradation products being linear low-molecular-weight polymers.
[0075] Example 4 In vitro GSH scavenging capacity and free radical generation capacity I. In vitro GSH clearance ability To simulate a tumor cell environment, the consumption of GSH was assessed using a colorimetric reaction between GSH and 5,5′-dithiobis(2-nitrobenzoic acid) (DTNB). The specific procedures were as follows: 0.08 mM aqueous solutions of GSH and DTNB were prepared. 1 mL of each solution was reacted with DTNB for 15 min, and then the spectra were scanned in the 200–800 nm range using a UV-Vis spectrophotometer to observe the maximum absorption wavelength.
[0076] GSH was dissolved in water, pH 5.5, and pH 7.4 buffer solutions to achieve a final concentration of 0.2 mM. 1 mg of P(MPC-ss-DMA)@Cu nanogel was weighed and added to 2 mL of GSH solutions (containing aqueous solutions) at different pH values. The solutions were ultrasonically dispersed and incubated at 37 °C for 15 min. After centrifugation (12000 rpm, 10 min), 0.5 mL of the supernatant was added to 1.5 mL of pH 8 buffer solution, followed by 0.5 mL of 0.2 mM DTNB aqueous solution. After incubation for 15 min, UV-Vis spectrophotometry was performed in the 200–800 nm range, and the absorbance at 409 nm was observed.
[0077] The results are as follows Figure 9 As shown. Figure 9 The results showed that P(MPC-ss-DMA)@Cu nanogels could effectively consume GSH, and the ability to consume GSH was stronger in the pH 7.4 environment than in the pH 5.5 environment. This is because the reducing ability of GSH is stronger in the pH 7.4 environment than in the pH 5.5 environment. In the reducing environment, the disulfide bonds inside the nanogel can consume GSH and reduce it to thiol groups, while Cu... 2+ It can also consume GSH to reduce it to Cu. +Therefore, P(MPC-ss-DMA)@Cu nanogel has GSH scavenging ability and can regulate the tumor microenvironment.
[0078] II. In vitro free radical generation capacity The ability of copper ion chelate nanogels to generate free radicals was detected by electron paramagnetic resonance (EPR) spectroscopy using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO). Without GSH, the procedure was as follows: 0.1 mL of 1 mg / mL chelate nanogel, 0.1 mL of 20 mM H₂O₂, and 30 μL of 100 mM DMPO were added to 1.8 mL of 0.01 M PBS buffer (pH 7.4). The reaction was carried out at room temperature for 15 min before measurement. With GSH, the procedure was as follows: 0.1 mL of 1 mg / mL chelate nanogel, 0.1 mL of 20 mM H₂O₂, 0.1 mL of 2 mM GSH, and 30 μL of 100 mM DMPO were added to 1.7 mL of 0.01 M PBS buffer (pH 7.4). The reaction was carried out at room temperature for 15 min before measurement.
[0079] The degradation of methylene blue (MB) under the action of hydroxyl radicals (·OH) was utilized. The degradation of MB was measured by monitoring the change in absorbance at 664 nm using UV-Vis light, thereby evaluating the ability of P(MPC-ss-DMA)@Cu nanogels to generate ·OH. The specific experimental steps were as follows: P(MPC-ss-DMA)@Cu nanoparticles (50 μg / mL) were dispersed in a mixture containing GSH (0.2 mM), H₂O₂ (2 mM), and MB (0.01 mM). The reaction was carried out at room temperature for a predetermined time. The reaction mixture was then centrifuged at 12000 rpm for 5 min, and the absorption spectrum of the supernatant was measured using a UV-Vis spectrophotometer in the wavelength range of 500–800 nm. Furthermore, the effect of temperature on MB degradation was investigated by conducting the reaction at different temperatures of 25 ℃, 37 ℃, and 55 ℃.
[0080] The results are as follows Figure 10 As shown. Figure 10 The results showed that P(MPC-ss-DMA)@Cu nanogels could catalyze the oxidation of H2O2 to produce ·OH, and the ability to produce ·OH was enhanced in the presence of GSH. Figure 10 a). The generated ·OH can promote the degradation of MB. The addition of GSH can enhance the ability of nanogel to catalyze the oxidation of H2O2 to generate ·OH and increase the degree of MB degradation. Figure 10(b, UV absorption at 664 nm is weakened); simultaneously, the ability to generate ·OH is stronger at pH 7.4 than at pH 5.5 ( Figure 10 c), and the ability to generate ·OH increases with increasing temperature ( Figure 10 d).
[0081] Example 5 Preparation of drug-loaded nanogels and their in vitro antitumor effects I. Drug Loading Experiment Doxorubicin (DOX), a first-line clinical antitumor drug, was selected as the model drug. 10 mg of P(MPC-ss-DMA) and P(MPC-ss-DMA)@Cu nanogels were dispersed separately in 2 mL of pure water, and 1 mg of DOX was dissolved in 1 mL of aqueous solution. The solutions were mixed and ultrasonically dispersed until homogeneous. The pH of the system was then adjusted to 8.0 with 0.1 M dilute NaOH aqueous solution and ultrasonically dispersed again. The mixture was placed in a suspension apparatus and mixed in the dark for 24 h. The DOX-loaded nanogels were collected by centrifugation and washed three times with pure water to remove surface-adsorbed DOX. The supernatant was collected, and the drug loading of the nanogels was determined by UV absorption spectroscopy to be 5.06%, with an encapsulation efficiency of 53.3%.
[0082] II. Tumor cytotoxicity assay (including copper inhibition assay) Using colon cancer cells (CT26) as the research subject, the CCK-8 assay was used to compare and analyze Cu. 2+ The difference in cytotoxicity of chelated nanogels to tumor cells before and after the addition of a copper inhibitor was investigated to evaluate the material's effect on cell proliferation. The specific procedures were as follows: First, cells were digested, counted, and prepared to a concentration of 8 × 10⁻⁶. 4 Cell suspension of cells / mL was prepared at 100 μL per well (8 × 10⁻⁶ cells / mL). 3 Cells were seeded in 96-well plates and incubated overnight at 37 °C with 5% CO2 to allow for cell adhesion. After cell adhesion, test working solutions containing different concentrations of the material were prepared using complete culture medium (90% DMEM + 10% fetal bovine serum). Before material treatment, 10 μM ammonium tetrathiomolybdate (ATTM) solution was added to the corresponding wells and pretreated at 37 °C for 4 h. Subsequently, 100 μL of the corresponding concentration of the material working solution was added to each well, with four replicates for each concentration. Cells were then cultured at 37 °C with 5% CO2 for 24 h. After culture, the supernatant was discarded, and the 96-well plates were stained with CCK-8 to measure the OD value (λ=450nm), and the cell proliferation rate was calculated accordingly.
[0083] The results are as follows Figure 11 As shown. Figure 11The results showed that P(MPC-ss-DMA)@Cu nanogel exhibited strong tumor cytotoxicity against colon cancer cells (CT26). At concentrations of 100 μg / mL and 200 μg / mL, cell viability decreased to approximately 50% and 20%, respectively. After the addition of the copper inhibitor ATTM, the cytotoxicity of P(MPC-ss-DMA)@Cu nanogel significantly decreased, and the cell viability increased to 104% and 73%, respectively. These results indicate that Cu in the nanogel... 2+ It can consume GSH in tumor cells and reduce it to Cu. + This catalyzes the oxidation of high levels of H2O2 in cells to produce a large amount of ·OH, thus significantly enhancing the oxidative stress level in tumor cells and effectively killing them. The addition of copper inhibitors can form stable complexes with copper ions, reducing the level of available copper ions in tumor cells and thus reducing tumor cell toxicity.
[0084] III. In vitro antitumor effects (synergistic evaluation) The ability of free DOX, P(MPC-ss-DMA)@DOX, P(MPC-ss-DMA)@Cu, and P(MPC-ss-DMA)@Cu-DOX nanogels to kill tumor cells was evaluated using colon cancer cells (CT26). The cell culture methods and specific procedures are as follows: cells were digested, counted, and prepared to a concentration of 5 × 10⁻⁶. 4 Add 100 μL of cell suspension per well (5 × 10⁶ cells / mL) to each well of a 96-well cell culture plate. 3 Cells were cultured in a 37 ℃, 5% CO2 incubator for 24 h. Working solutions of 0.5–10 μg / mL free DOX, P(MPC-ss-DMA)@DOX nanogels with equal DOX concentrations, P(MPC-ss-DMA)@Cu nanogels with Cu concentrations equal to DOX concentrations, and P(MPC-ss-DMA)@Cu-DOX nanogels with equal DOX and Cu concentrations (the sum of DOX and Cu concentrations equals the free DOX concentration) were prepared using complete culture medium (90% DMEM + 10% fetal bovine serum). 100 μL of the corresponding working solution was added to each well, with three replicates for each concentration. Cells were cultured in a 37 ℃, 5% CO2 incubator for 48 h, and the supernatant was discarded. The 96-well plate was stained with CCK-8, and the OD value was measured at λ = 450 nm. Calculate cell viability (Viability%) and inhibition rate (Fa, inhibition rate = 1 - viability%).
[0085] Table 3 shows the inhibition rate (Fa value) of CT26 cells in each treatment group at different concentrations. From Table 3 and... Figure 12It is evident that the CDT group alone (P(MPC-ss-DMA)@Cu), the chemotherapy group alone (P(MPC-ss-DMA)@DOX), and the synergistic group (P(MPC-ss-DMA)@Cu-DOX) all exhibited significant inhibitory effects on CT26 tumor cells. While the CDT and chemotherapy groups alone showed inhibitory effects on tumor cells, their inhibitory effects were limited in the low concentration range (0.5-2.0 μg / mL). For example, at 1.0 μg / mL, the inhibition rates of both groups did not exceed 20%. The synergistic group, however, demonstrated significant killing power at the same concentration, achieving an inhibition rate of 45% at 1.0 μg / mL, significantly higher than the theoretical sum of the CDT and chemotherapy groups alone (19% + 18% = 37%).
[0086] Table 3. Inhibition rate of CT26 cells at different concentrations in each treatment group (Fa value) (Mean ± SD, n=3) Example 6 In vivo tumor suppression effect 5×10 6 One CT26 cell (dispersed in 100 μL PBS) was subcutaneously injected into the left axilla of each male Balb / c mouse to establish a CT26 tumor-bearing mouse model. Tumor volume was calculated using the following formula: Tumor volume = 0.5 × length × width 2 When the tumor volume reaches approximately 100 mm 3 Mice were randomly divided into six groups (n=5 per group) and given the following treatments: (1) PBS control group; (2) P(MPC-ss-DMA) (100 mg / kg); (3) P(MPC-ss-DMA)@Cu (equivalent Cu dose of 5 mg / kg); (4) Free DOX (5 mg / kg); (5) P(MPC-ss-DMA)@DOX (equivalent DOX dose of 5 mg / kg); (6) P(MPC-ss-DMA)@Cu-DOX (equivalent (Cu dose + DOX dose) of 5 mg / kg, Cu dose = DOX dose). Each group was injected into the body via the tail vein on days 0, 3, 6 and 9. The weight and tumor volume of the mice were measured every other day. On day 14, the mice in each group were sacrificed in accordance with animal ethics. Their major organs (heart, liver, spleen, lung and kidney) and tumors were removed, fixed with 4% paraformaldehyde, and the mass of the tumors was measured. Data are expressed as Mean ± SD (n = 5); p > 0.05 indicates no statistical difference (ns); p < 0.05 indicates a significant difference (*); p < 0.01 indicates a highly significant difference (**); p < 0.001 indicates an extremely significant difference (***).
[0087] I. Changes in tumor volume The tumor volume change curves of mice in each experimental group during the treatment process are shown in the figure below. Figure 13 As shown, tumors in untreated control mice grew rapidly, reaching an average tumor volume of 1445 mm on day 14. 3 After 14 days of treatment, the mean tumor volume in the blank nanogel group (P(MPC-ss-DMA)) was 1388 mm. 3 There was no significant therapeutic effect on tumors; the average tumor volume on day 14 of treatment in the P(MPC-ss-DMA)@Cu group, the free DOX group, and the P(MPC-ss-DMA)@DOX group was 594 mm. 3 (Tumor inhibition rate 58.9%), 664 mm 3 (tumor inhibition rate 54.1%) and 348 mm 3 (Tumor inhibition rate 75.9%). In comparison, the mean tumor volume in the P(MPC-ss-DMA)@Cu-DOX group was 195 mm. 3 The tumor inhibition rate was 86.5%, demonstrating the best tumor inhibition effect.
[0088] II. Changes in Tumor Weight The weight of tumors removed from mice in each experimental group after treatment is as follows: Figure 14 As shown in the figure, the mean tumor weights of mice in the PBS control group, P(MPC-ss-DMA) group, P(MPC-ss-DMA)@Cu group, free DOX group, P(MPC-ss-DMA)@DOX group, and P(MPC-ss-DMA)@Cu-DOX treatment group were 1.13 g, 0.96 g, 0.64 g, 0.66 g, 0.46 g, and 0.18 g, respectively. Among them, the mean tumor weight of mice treated with P(MPC-ss-DMA)@Cu-DOX group was the lowest, indicating that P(MPC-ss-DMA)@Cu-DOX group has a significant synergistic anti-tumor effect.
[0089] III. Changes in mouse body weight The curves showing the change in body weight over time in each experimental group of mice during treatment are as follows: Figure 15 As shown in the figure, during the 14-day tumor suppression experiment, compared with the PBS control group, mice treated with P(MPC-ss-DMA), P(MPC-ss-DMA)@Cu, P(MPC-ss-DMA)@DOX, and P(MPC-ss-DMA)@Cu-DOX did not show significant weight loss. However, the weight of mice in the free DOX group gradually decreased from 19.4 g to 18.1 g during treatment, indicating DOX-induced systemic toxicity. Meanwhile, the weight of mice in the P(MPC-ss-DMA)@Cu-DOX treatment group increased from approximately 20 g to approximately 21 g, indicating that the health status of the mice was not affected after treatment.
Claims
1. A copper ion-chelated zwitterionic polymer nanogel, characterized in that, The nanogel is prepared by the following methods or has the following structure: The nanogel is a cross-linked copolymer, and its backbone is composed of the following monomer units: (a) A zwitterionic monomer unit, wherein the zwitterionic monomer is 2-methacryloyloxyethylphosphorylcholine; (b) A monomer unit containing a catechol group, wherein the monomer containing the catechol group is dopamine methacrylamide; The crosslinked copolymer is crosslinked via a crosslinking agent unit containing disulfide bonds, wherein the crosslinking agent containing disulfide bonds is N,N'-bis(acryloyl)cystamine; Furthermore, the nanogel reacts with copper ions (Cu) via the phenolic hydroxyl groups on the monomer units containing catechol groups. 2+ Coordination occurs, thereby chelating copper ions.
2. The zwitterionic polymer nanogel according to claim 1, characterized in that, In the nanogel, the monomer units derived from dopamine methacrylamide account for 10% to 70% of the total monomer units by mass, preferably 50%.
3. The zwitterionic polymer nanogel according to claim 1 or 2, characterized in that, The nanogel has a particle size of 200~310 nm, a polydispersity index ≤0.22, and a zeta potential of -2.95 ~ -11.6 mV; preferably, the particle size is 263.52 nm, the polydispersity index is 0.007, and the zeta potential is -7.08 mV.
4. The copper ion-chelated zwitterionic polymer nanogel according to claim 1, characterized in that, In the nanogel, the mass ratio of copper chloride to the nanogel is 1:10 to 1:5, preferably 1:8; and the copper loading rate of the nanogel is 4.12% to 8.54%, preferably 5.26%.
5. The copper ion-chelated zwitterionic polymer nanogel according to claim 1, characterized in that, The nanogel is also loaded with the antitumor drug doxorubicin; preferably, the nanogel has a drug loading of 5.06% for doxorubicin and an encapsulation rate of 53.3%.
6. The method for preparing copper ion-chelated zwitterionic polymer nanogels according to any one of claims 1-4, characterized in that, Includes the following steps: Step (1): 2-methacryloyloxyethyl phosphorylcholine, dopamine methacrylamide, N,N'-bis(acryloyl)cysteine and azobisisobutyronitrile were dissolved in acetonitrile and reacted at 80~100 °C for 30~60 minutes under inert gas protection. After cooling, centrifugation, washing and drying were performed to obtain P(MPC-ss-DMA) nanogel. Step (2): Disperse the P(MPC-ss-DMA) nanogel obtained in step (1) in a buffer solution with pH 8~10, add copper chloride solution, stir at room temperature for 2~6 hours to allow copper ions to coordinate with the phenolic hydroxyl groups in the nanogel. After the reaction is completed, centrifuge, wash and dry to obtain the copper ion chelated zwitterionic polymer nanogel.
7. The preparation method according to claim 6, characterized in that, In step (1), the mass ratio of 2-methacryloyloxyethyl phosphorylcholine, dopamine methacrylamide and N,N'-bis(acryloyl)cystamine is 100:100:40; in step (2), the mass ratio of copper chloride and P(MPC-ss-DMA) nanogel is 1:
8.
8. A method for preparing a copper ion-chelated zwitterionic polymer nanogel loaded with doxorubicin, characterized in that, Includes steps (1) and (2) as described in claim 6, and the following step (3): mix the copper ion chelated zwitterionic polymer nanogel prepared by the method of claim 6 or 7 with doxorubicin, mix for 18 to 48 hours under light-protected conditions, centrifuge and wash to obtain the final product.
9. The use of the copper ion chelated zwitterionic polymer nanogel according to any one of claims 1-7 or the copper ion chelated zwitterionic polymer nanogel loaded with doxorubicin prepared according to the method of claim 8 in the preparation of a drug for treating tumors.
10. The application according to claim 9, characterized in that, The tumor is colon cancer.
Citation Information
Patent Citations
Nanogel and nanogel drug carrier system both with smart response to tumor microenvironment
CN106810636A
Zwitterionic polymer nanogel as well as preparation method and applications thereof
CN108379219A
Preparation and application of biodegradable nano-enzyme based on zwitterionic polymer gel
CN117467074A
Zwitterionic nanogel and application thereof
CN119930924A